2010
DOI: 10.1073/pnas.1011090108
|View full text |Cite
|
Sign up to set email alerts
|

Family level phylogenies reveal modes of macroevolution in RNA viruses

Abstract: Despite advances in understanding the patterns and processes of microevolution in RNA viruses, little is known about the determinants of viral diversification at the macroevolutionary scale. In particular, the processes by which viral lineages assigned as different "species" are generated remain largely uncharacterized. To address this issue, we use a robust phylogenetic approach to analyze patterns of lineage diversification in five representative families of RNA viruses. We ask whether the process of lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 34 publications
2
99
0
1
Order By: Relevance
“…With the exception of Theilovirus, the host range of these species was expanded as a result of this virus update. A recent phylogenetic study of RNA viruses from three families and two genera other than the Picornaviridae revealed that host switching by virus species is more frequent than previously thought (38).…”
Section: Resultsmentioning
confidence: 97%
“…With the exception of Theilovirus, the host range of these species was expanded as a result of this virus update. A recent phylogenetic study of RNA viruses from three families and two genera other than the Picornaviridae revealed that host switching by virus species is more frequent than previously thought (38).…”
Section: Resultsmentioning
confidence: 97%
“…19 However, the lack of antibodies to BRSV and BPIV-3 in a larger sample of rats may be a further indication that rats in this population were not exposed to respiratory paramyxoviruses that may induce crossreactive antibodies to these and related viruses. 25 A recent study of 114 wild rats from New York City also did not identify paramyxoviruses. 13 In a previous study, the seroprevalence to rat coronavirus in wild rats was 92% but was only 4% to Sendai virus.…”
Section: Discussionmentioning
confidence: 99%
“…paramyxoviruses | respiratory syncytial viruses | human parainfluenza | pathogen interactions | cross-immunity R espiratory Syncytial Virus (RSV) and Human Parainfluenza Virus (HPIV), two important closely related members in the Paramyxovirus family (1), are leading causes of hospitalization in young children with community-acquired respiratory disease (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Each year, they impose a huge burden on public health by demanding substantial healthcare system resources (14).…”
mentioning
confidence: 99%